Replicating: "Playing Politics with Environmental Protection: The Political Economy of Designating Protected Areas" - Laura Villalobos; Jill Caviglia-Harris; Tharaka Jayalath (Institute for Replication (I4R), 2023)
Mangonnet et al. (2022) examine whether political alignment at the national and sub-national levels explain the spatial designation of Protected Areas (PAs) in Brazil. Their identification relies on spatial discontinuities in political alignment across municipalities. They find that a president-mayor coalition alignment reduces the incidence of PAs by about one percentage point, whereas they find no party alignment effects. We were able to reproduce the paper's findings using the same code and software. Alternative software routines reproduce their results with small and inconsequential numerical differences. Moreover, robustness replications find consistent results for one out the two treatments. Finally, we find no evidence of fabrication of data.
Keywords: 330; replication study; robustness replicability; reproducibility